Characteristics of Guava Juice Powder Which is Dried by Foam Mat Drying Method - Ramadhani Nurbaya, Syarifa; Azara, Rima; Prihatiningrum, Andriani Eko; Kinanti, Kintan Sari (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the chemical and physical characteristics of guava juice powder which is dried by the foam mat drying method. The research design used was two factor randomized group design. The first factor was maltodextrin concentration (5%, 10%, 15%). The second factor was the concentration of egg whites (3%, 6%, 9%). Parameters observed were: water content, vitamin A content, vitamin C content, and yield. Based on observational data, the interaction between maltodextrin concentration and egg white had a significant effect on vitamin A content in guava juice powder. The best treatment was found in the maltodextrin concentration of 15% and egg white concentration of 9% which had a water content value of 2.77%, vitamin A content of 0.18%, vitamin C content of 0.003%, and yield of 15.46%. Red guava juice powder can be one of the instant drink powder products using natural ingredients.